Venoms of Neotropical wasps lack cross-reactive carbohydrate determinants enabling reliable protein-based specific IgE determination - Perez-Riverol, Amilcar; Miehe, Michaela; Jabs, Frederic; Seismman, Henning; Romani Fernandes, Luís Gustavo; de Lima Zollner, Ricardo; Jakob, Thilo; Brochetto Braga, Marcia R.; Spillner, Edzard (Journal of allergy and clinical immunology, 2018)
Systematic studies showed that in contrast to Europe and Northern America, the most commonly found wasp species in Neotropical regions belong to the Epiponini tribe of the Polistinae subfamily including, for example, the genera Polybia, Apoica, and Agelaia.3 Despite the high incidence, the severity of sting events, and the broad diversity of clinically relevant Hymenoptera identified in this geographical zone, venom allergy diagnosis is essentially based on either commercial venom extracts from European and North American species, or noncommercial venoms from endemic species. While allergen components remain unavailable, crude venoms from these species allow for reliable determination of CCD-independent sensitization. [...]the differentiation of sensitization to HBV or wasp venom is significantly facilitated in particular in those patients having sIgE to CCDs. Because of frequent lack of information, positive sIgE to these venoms now can be interpreted as a purely venom-based sensitization in patients with and without sIgE to CCDs. [...]the quantitative determination of sIgE levels to venoms of wasps from different tribes might allow the identification of culprit insects even within taxonomically related species.